APPLYING COMMUNICATIVE LANGUAGE TEACHING (CLT) TO ENHANCE EARLY ENGLISH SPEAKING IN KINDERGARTEN - Tolibekova, Feruza Minajatdinovna; Dauletmuratova, Xurziya Elubaevna (ILIM hám JÁMIYET, 2026)
The article explores the use of Communicative Language Teaching (CLT) in teaching English to kindergarten learners. It investigates how interactive activities such as games, flashcards, role-plays, and songs influence children’s vocabulary learning and participation. The research was conducted through classroom-based action research in a preschool setting with learners aged 4-6. Findings show that CLT increases student engagement, motivation, and basic vocabulary use, although language output remains limited to simple words and short phrases. The study concludes that CLT is effective for early language learning, especially in large and interactive classrooms.